2021
DOI: 10.3390/ma14112839
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Resistance of Laser Cladding of Fe-Based Alloy Coatings in Different Areas of Cladding Layer

Abstract: In this study, laser cladding technology was used to prepare Fe-based alloy coating on a 27SiMn hydraulic support, and a turning treatment was used to obtain samples of the upper and middle regions of the cladding layer. The influence of microstructure, phase composition, hardness, and wear resistance in different areas of the cladding layer was studied through scanning electron microscopy (SEM), X-ray diffractometry (XRD), friction and wear tests, and microhardness. The results show that the bcc phase content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…It can be concluded that the main wear mechanism is adhesive and abrasive wear. Similar conclusions were reported by Q. Bai et al [ 36 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It can be concluded that the main wear mechanism is adhesive and abrasive wear. Similar conclusions were reported by Q. Bai et al [ 36 ].…”
Section: Resultssupporting
confidence: 92%
“…At the beginning of the wear test, the Cof fluctuates because the contact between the coating and counter-body (the WC ball) is small with a large contact stress leading to an increased Cof. After that, the contact stress continues to decrease and the Cof tends to stabilize [ 36 ]. It can be also seen that all the coatings present uneven curves which is attributed to an uneven carbide distribution throughout the coatings.…”
Section: Resultsmentioning
confidence: 99%
“…However, the production of hazardous hexavalent chromium compounds during electroplating has encouraged industry to employ thermal spray coatings rather than hard chrome plating [ 54 ]. Laser cladding is also being researched to repair the surface of moulds [ 55 ]. Thin solid films have been implemented to protect SENs and mould linings [ 56 ], but these have limited effectiveness under the highly aggressive industrial conditions.…”
Section: Thermal Spray Applications In Iron and Steel Industrymentioning
confidence: 99%
“…For the AlxCo 1.5 CrFeNi 1.5 Tiy high-entropy alloys investigated by Chuang et al [22], Co 1.5 CrFeNi 1.5 Ti and Al 0.2 Co 1.5 CrFeNi 1.5 Ti alloys are found to have better wear resistance at least two times than that of conventional wear-resistant steels SUJ2 and SKH51with similar hardness. HEAs coatings prepared by laser cladding characterized as excellent wear resistance and bonding strength have got considerable attention in recent years [23,24]. Juan et al [25].…”
Section: Introductionmentioning
confidence: 99%